IDENTIFICATION OF POLYMORPHISM OF FSH BETA-SUBUNIT GENE AS SPERM QUALITY MARKER IN BALI CATTLE USING PCR-RFLP - Ishak, A.B.L.; Sumantri, C.; Noor, R.R.; Arifiantini, I. (Diponegoro University, 2011)
The aim of study was to identify the association of FSH beta-subunit gene polymorphisms withsperm quality traits. A total of 470 samples of normal mature bull from several breeds were used forpopulation study and 127 bulls from National and Regional AI centre of Indonesia for association study.To amplify, a PCR-RFLP method was used and digested with Pst1 restriction enzyme. The allelefrequency of the A and B in Bali cattle were (0.000) and (1.000), respectively. The absence of otherallele A suggested that the Bali cattle was monomorphic, while Brahman, FH, Simmental and Limousinewere polymorphic. The highest observed heterozygosity were found in Limousine (0.318) and thehighest expected heterozygosity were in Simmental (0.420). The higher incident of percentage of spermabnormalities were found in Simmental, Limousin, Brahman compared to Bali and FH. Among all typesof sperm abnormalities, the abaxial and microcephalus were found in highest number.